Development of Interactive Learning Media with InShot Application in Arabic Language Subjects - Parikesit, Bintang; Amrullah, Muhammad Afif (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This research aims to develop interactive learning media using the InShot application for Arabic language instruction and to validate its effectiveness through evaluations by material experts, media experts, and student trials. The study employs a Research and Development (R&D) approach following the ADDIE model, combining qualitative methods through direct interviews with Arabic language teachers and quantitative methods via media and material validation. The development of digital technology has significantly transformed education, requiring teachers to creatively integrate technology-based learning media to enhance student engagement and comprehension. Despite various learning media being available, there remains a gap in utilizing multimedia applications like InShot to create interactive and engaging Arabic learning materials. The results indicate that the interactive media developed with InShot effectively increases students’ interest, motivation, and understanding of Arabic content. Validation tests confirm that the product is highly feasible for classroom use. In conclusion, employing the InShot application as an interactive learning tool enhances both learning effectiveness and student motivation, and its development is recommended as an innovative alternative for digital learning in the modern era.